PENGGUNAAN MEDIA KARTU BERSUSUN TERHADAP KEMAMPUAN MEMBACA KALIMAT BERPOLA PADA SISWA SEKOLAH DASAR KELAS V - Karin Widya Ayuningtyas; Panca Dewi Purwati; Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Indonesian language learning in grade 5 at SD Negeri Songgom 01, especially thematerial on patterned sentences, often faces obstacles in improving studentsunderstanding of the correct sentence structure. One of the causes is thatstudents have difficulty when reading patterned sentences and identifying them.Innovative learning media in the form of stacked cards by applying the PBLlearning model is needed to overcome these problems. The subjects of this studywere fifth grade students of SDN Songgom 01, totaling 20 students. This studyaims to determine the effect of using Stacked Card learning media in improvingthe ability to read patterned sentences. This research uses mixed methods withparallel convergent design by collecting quantitative and qualitative datasimultaneously and analyzed separately. The results of quantitative analysisshowed an increase in students ability to read patterned sentences when usinglearning media. The qualitative analysis results show that the application ofStacking Card media through PBL mode learning is able to increase studentsdemand to read patterned sentences so that students actively participate and areable to master the structure of sentence patterns. The social benefit of this mediaapplication is to improve students' communication and social skills, because theylearn to work together in groups to complete tasks in the form of sentences.